아로마 마사지가 림프부종에 미치는 영향 - 김성중; Sung Joong Kim; 심정묘; Jung Myo Shim; 박용덕; Yong Deok Park (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2007)
The purpose of this study was to determine whether aromatherapy massages with manual lymph drainage (MLD) are significantly more effective than sham massages with MLD in reducing edematous limb volume in lymphedema. This study was performed on 46 patients who had developed unilateral upper or lower lymphedema. Twenty-three patients served as the experimental group and were treated with complex decongestive physiotherapy (CDP) applications including aroma massages with MLD, multi layered compression bandages, remedial exercises and skin care. Twenty-three patients in the control group were treated with CDP applications including sham massages with MLD, bandages, exercises and skin care. Patients undergo a therapy program once a day; 5 days a week for 2 weeks. Percentage excess volume (PEV) and body mass index (BMI) were recorded before and after treatment. PEV and BMI were significantly decreased before and after treatment in the experimental as well as in the control groups (p<.05). However, the percentage excess volume and BMI were not significantly improved after treatment between the two groups (p>.05). This study there suggests that aroma massages is not effective in the edema of patients with lymphedema.